FABRICATION OF ALL PORCELAIN CANTILEVER BRIDGE RESTORATION IN CASES OF GINGIVA RECESSION USING ZIRCONIUM DIOXIDE MATERIAL WITH ADDITIONAL RETENSION - Pauline, Yobellivia; Inayati, Eny; Goenharto, Sianiwati; Setyowati, Okti; Kusdaryanti, Endang; Redjeki Indiani, Sri; Mia Laksmi Lita Rosa (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Aesthetic and functional dental restoration is a hope for people who have lost teeth, especially in the anterior region. Missing tooth 13 with more than 2 mm gingival recession can be made into a cantilever bridge restoration with the addition of porcelain gingiva. Gingival recession is when the tooth root surface is exposed due to periodontal tissue loss. Zirconia is a dental restoration material often used because of its biocompatibility, strength, and aesthetics. Purpose: To determine the procedure for making all porcelain cantilever bridge restorations in cases of gingival recession using zirconia material. Case analysis: The dental laboratory received a dental cast model of a 39-year-old female patient missing tooth 13 and had gingival recession on tooth 14 of more than 2 mm. Order in the form of restoration of all porcelain cantilever bridges from zirconia. Result: The cantilever bridge coping was made from zirconium dioxide and then layered with feldspathic porcelain to achieve optimal strength and aesthetics. A rest is made on tooth 12 to provide additional retention. Conclusion: The procedure for making all porcelain cantilever bridge restorations includes making diagnostic wax-up, scanning, coping design, milling, sintering, fitting, sandblasting, layering, anatomy, and glazing. Things that must be considered are the design, thickness of the coping, and connectors to achieve a restoration that is strong, resistant to fracture, and has good aesthetics. Porcelain gingiva was added in the cervical area of tooth 14 restorations to cover the recession